Brachypodium distachyon is a pathosystem model for the study of the wheat disease rhizoctonia root rot. (6th May 2014) - Schneebeli, K.; Mathesius, U.; Watt, M.
<x xml:space="preserve">Abstract</x> Brachypodium distachyon (Bd) is increasingly being used as a model for cereal diseases and to study cereal root architecture. Rhizoctonia solani AG 8 is a necrotrophic root pathogen that infects wheat soon after germination resulting in reduced plant growth and yield loss. Genetic resistance to R. solani AG 8 is not available in commercial wheat cultivars, although some quantitative levels of resistance have previously been found in mutant lines and grass relatives. Resistance mechanisms in cereals remain unknown. The ability to use Bd as a model to study the wheat–R. solani AG 8 pathosystem was investigated. The results presented show that Bd is susceptible to R. solani AG 8 and that the pathogen infects both species to a similar degree, producing comparable disease symptoms. Root length reduction was the primary indicator of disease, with shoots also affected. The second objective was to develop a repeatable phenotyping method to screen Bd populations for resistance to R. solani AG 8. Results of a preliminary experiment provide evidence for variation in resistance between Bd inbred lines. This is the first report showing the potential of Bd as a model plant for discovery of quantitative genetic variation in resistance to a necrotrophic cereal root pathogen.